Geographic and Spatial Assimilation of Immigrants from Central America's Northern Triangle. (22nd February 2019) - Obinna, Denise N.; Field, Layton M.
Abstract: With declines in migration from Mexico, the countries of the Northern Triangle of Central America (NTCA) – El Salvador, Honduras and Guatemala – are now responsible for some of the largest increases in the population density of Latinos in the United States. Using data from the 5‐year estimates of the 2016 American Community Survey and the Atlas of Rural and Small‐Town America, this article provides a spatial framework for settlement among NTCA immigrants in America. Findings illustrate that, unlike previous streams of Latino migration, which tended to be more agriculturally driven, NTCA immigrants are likely to choose settlement destinations in densely populated counties which support manufacturing rather than those which are farming dependent. We also find that while NTCA communities are predominant in new destinations like Prince Georges and Montgomery counties Maryland, they are also dominant in older Latino destinations like Harris County, Texas and Los Angeles county, California.